Study on cancer prevention strategy by Punica granatum: the role of polyamines in regulating cell cycle and cell death in human lung carcinoma A549 cells - Nik Abdul Malek, Nik Nurasyikin; Abdul Ghani, Radiah (2016)
Cancer is a complex disease to treat and the treatments have not progressed significantly in the last few years. Alternative strategies such as chemoprevention need to be explored. Punica granatum or known as pomegranate has a potential to be a useful chemopreventive agent, however the mechanism of action is unclear. To understand how effective the P.granatum in preventing cancer growth, it is crucial to identify the signaling pathways affected. One possibility is the polyamine pathway which is important in many cells function and its up-regulation of this pathway in cancer makes it a logical target for chemoprevention. Therefore, this study was aimed to evaluate the role of polyamines in cell cycle, cell death mechanism and its anti-proliferative effect in human lung carcinoma A549 cells. The cytotoxicity activity of pomegranate juice was tested by using MTT assay and the effect of 2% pomegranate juice on A549 cells growth and viability were evaluated by trypan blue exclusion assay. The protein and polyamines content were determined using Lowry assay and HPLC, respectively. The cell cycle distribution and cell death mechanisms were evaluated using flow cytometer. The gene expression was evaluated using quantitative real - time PCR. The result showed that pomegranate juice at the concentration range from 0.0 to 3.0% had resulted inhibition of A549 cells growth. The inhibitory concentration (IC50) was 1.4% ± 0.23, 1.5% ± 0.14 and 1.4% ± 0.12 after 48, 72 and 96 hour exposure, respectively. At the concentration of 2%, inhibition of growth was observed by showing decreased in cell number and protein content after 48 hour exposure (p<0.05), 72 hour exposure (p<0.001) and 96 hour exposure (p<0.001) compared to untreated cells. In contrast, the percentage of cells viability remains high and constant. The results also showed positive correlation between total A549 cells number with protein content where the R2 values for untreated and treated were 0.9248 and 0.6523. The total polyamine detected in the pomegranate juice was classified as low (less than 100 nmole/ml). The level of intracellular polyamines decreased compared to untreated cells where the individual polyamine that contribute to the decreasing pattern was putrescine. It has also been found that the pomegranate juice induced cell cycle arrest at S phase in A549 cells and caused a loss of mitochondrial membrane permeability where the percentage of depolarized cells increased after 48 hour exposure (p<0.05). Caspases study showed the activation of caspase 3 after 72 hour exposure (p<0.01) and caspase 9 after 48 (p<0.01) and 72 hour exposure (p<0.05). Gene expression study also showed inhibition of Ornithine decarboxylase (ODC) gene expression, after 24 and 48 hour exposure (p<0.05). However, the gene expression of Spermidine/spermine N1-transferase (SSAT) was not induced. In conclusion, pomegranate juice caused growth inhibition due to depletion of polyamines which led to cell death. Therefore, it can be deduced pomegranate juice induced polyamine pathway in A549 cells through intrinsic pathway by activation of caspase 9.